Flow volume measurement of arterial venous and cerebrospinal fluid in patients with multiple sclerosis - Aglamis, Serpil; Gonen, Murat (Assoc Arquivos Neuro- Psiquiatria, 2022)
Background Multiple sclerosis (MS) is usually described as an autoimmune disease, although the exact mechanism of the disease remains unknown. There have been studies reporting that venous flow abnormalities may be involved in the pathogenesis of MS or many of the associated clinical manifestations. Objective The aim of this study was to evaluate flow volumes of the middle cerebral artery (MCA), transverse sinus (TS), and cerebral aqueduct using phase contrast magnetic resonance imaging (PC-MRI) in relapsing-remitting MS patients and a control group. Methods We included 34 patients diagnosed by the McDonald criteria, revised in 2017, as well as 15 healthy controls matched by age and sex. The MRI scans were performed using a 1.5-T superconducting scanner. Axial T1-weighted, T2-weighted, and PC-MRI sequences were performed for the quantitative investigation of flow volume measurements. Quantitative analyses of flows were performed using flow analyses program PC-MRI angiography software. A circular region of interest was placed manually into the cerebral aqueduct, bilateral MCA, and TS. Results Flow volumes of the cerebral aqueduct and MCA were not statistically significant between the MS and control groups. The flow volumes of the TS for the patient group were lower than those of the control group, and this difference was statistically significant. Conclusions A reduced TS flow volume in MS patients was noted in the present study when compared with the control group, suggesting a relation between venous pathologies and MS. Further studies are needed to understand whether this relation is causal or epiphenomenal.
Medição do volume de fluxo do líquido cefalorraquidiano e venoso arterial em pacientes com esclerose múltipla
Keywords: Multiple Sclerosis; Magnetic Resonance Imaging; Middle Cerebral Artery; Transverse Sinuses